National security in Malaysia's digital economy: redefinition, reaction and legal reform - Zulhuda, Sonny (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
This paper investigates the need for Malaysia to relook at and redefine the concept of national security amid the changing circumstances especially in relation to the country’s increased reliance on the information and communications technology (hereinafter, ICT). The more a governance system is exposed to the Internet and ICT, the bigger the risks it would face. When the security of the system is not reliable enough to secure the system, information assets are at stake and the country’s critical information infrastructure (such as defence, communications, energy and medical systems) will become loophole that undermines national security. At the end, the paper examines Malaysia’s policy and legal initiatives it has set to adopt. While steps have been taken to provide necessary policies and strategies, it is argued that the law on national security requires a fresh look and interpretation in order to support the protection of national critical information infrastructure.